COVID-19 and Its Implications for the Practice of Psychotherapy on Zoom during the Pandemic. Issue 2 (1st September 2022) - Haynes, Jane
Abstract: As a result of the pandemic, I am a fugitive from my Marylebone consulting rooms. I have had to adapt my 'technique' to both the limitations and extended possibilities of Zoom. To mirror back a patient's psyche in an accelerating emotional climate of existential anxiety and increased irritability. I refer to the 'democratisation' of therapy brought about by the increased autonomy of the patient to control their environment and access to intimacy during Zoom sessions. One of the most painful realities of being controlled by technology is its crudity, its totalitarianism in comparison to mediated physical contact engaged in face-to-face work. Clinical vignettes (always with the patient's written consent) are provided to demonstrate clinical phenomena unique to the Zoom setting.